Demand creation for HIV testing services: A systematic review and meta-analysis. - Anjuli D Wagner; Irene N Njuguna; Jillian Neary; Kendall A Lawley; Diana K N Louden; Ruchi Tiwari; Wenwen Jiang; Ngozi Kalu; Rachael M Burke; Dorothy Mangale; Chris Obermeyer; Jaclyn N Escudero; et al. (PLoS Medicine)
Background HIV testing services (HTS) are the first steps in reaching the UNAIDS 95-95-95 goals to achieve and maintain low HIV incidence. Evaluating the effectiveness of different demand creation interventions to increase uptake of efficient and effective HTS is useful to prioritize limited programmatic resources. This review was undertaken to inform World Health Organization (WHO) 2019 HIV testing guidelines and assessed the research question, "Which demand creation strategies are effective for enhancing uptake of HTS?" focused on populations globally. Methods and findings The following electronic databases were searched through September 28, 2021: PubMed, PsycInfo, Cochrane CENTRAL, CINAHL Complete, Web of Science Core Collection, EMBASE, and Global Health Database; we searched IAS and AIDS conferences. We systematically searched for randomized controlled trials (RCTs) that compared any demand creation intervention (incentives, mobilization, counseling, tailoring, and digital interventions) to either a control or other demand creation intervention and reported HTS uptake. We pooled trials to evaluate categories of demand creation interventions using random-effects models for meta-analysis and assessed study quality with Cochrane's risk of bias 1 tool. This study was funded by the WHO and registered in Prospero with ID CRD42022296947. We screened 10,583 records and 507 conference abstracts, reviewed 952 full texts, and included 124 RCTs for data extraction. The majority of studies were from the African (N = 53) and Americas (N = 54) regions. We found that mobilization (relative risk [RR]: 2.01, 95% confidence interval [CI]: [1.30, 3.09], p < 0.05; risk difference [RD]: 0.29, 95% CI [0.16, 0.43], p < 0.05, N = 4 RCTs), couple-oriented counseling (RR: 1.98, 95% CI [1.02, 3.86], p < 0.05; RD: 0.12, 95% CI [0.03, 0.21], p < 0.05, N = 4 RCTs), peer-led interventions (RR: 1.57, 95% CI [1.15, 2.15], p < 0.05; RD: 0.18, 95% CI [0.06, 0.31], p < 0.05, N = 10 RCTs), motivation-oriented counseling (RR: 1.53, 95% CI [1.07, 2.20], p < 0.05; RD: 0.17, 95% CI [0.00, 0.34], p < 0.05, N = 4 RCTs), short message service (SMS) (RR: 1.53, 95% CI [1.09, 2.16], p < 0.05; RD: 0.11, 95% CI [0.03, 0.19], p < 0.05, N = 5 RCTs), and conditional fixed value incentives (RR: 1.52, 95% CI [1.21, 1.91], p < 0.05; RD: 0.15, 95% CI [0.07, 0.22], p < 0.05, N = 11 RCTs) all significantly and importantly (≥50% relative increase) increased HTS uptake and had medium risk of bias. Lottery-based incentives and audio-based interventions less importantly (25% to 49% increase) but not significantly increased HTS uptake (medium risk of bias). Personal invitation letters and personalized message content significantly but not importantly (<25% increase) increased HTS uptake (medium risk of bias). Reduced duration counseling had comparable performance to standard duration counseling (low risk of bias) and video-based interventions were comparable or better than in-person counseling (medium risk of bias). Heterogeneity of effect among pooled studies was high. This study was limited in that we restricted to randomized trials, which may be systematically less readily available for key populations; additionally, we compare only pooled estimates for interventions with multiple studies rather than single study estimates, and there was evidence of publication bias for several interventions. Conclusions Mobilization, couple- and motivation-oriented counseling, peer-led interventions, conditional fixed value incentives, and SMS are high-impact demand creation interventions and should be prioritized for programmatic consideration. Reduced duration counseling and video-based interventions are an efficient and effective alternative to address staffing shortages. Investment in demand creation activities should prioritize those with undiagnosed HIV or ongoing HIV exposure. Selection of demand creation interventions must consider risks and benefits, context-specific factors, feasibility and sustainability, country ownership, and universal health coverage across disease areas.